Nutritional composition, phytochemicals, and antioxidant activities of Abies marocana Trab. needles - Zirari, Malak; Aouji, Marouane; Imtara, Hamada; Hmouni, Driss; Tarayrah, Mahmoud; Noman, Omar M.; El Mejdoub, Nouredine (Frontiers in Sustainable Food Systems, 2024)
Finding natural sources of bioactive compounds is turning into a cutting-edge task for the scientific community and industry alike. Abies marocana, Moroccan fir, holds great importance due to its ecological, economic, social, and cultural significance. The current study aimed to evaluate the needles of Abies marocana in terms of its nutritional and anti-nutrient content, bioactive components, and antioxidant capacity. The AOAC technique was used to determine the composition of the needles. Mineral content was analyzed by inductively coupled plasma optical emission spectrometry. Phytochemical screening of methanol extract was performed using standard procedures, and multiple assays evaluated antioxidant activity. The extract's volatile profile was elucidated using GC-MS method. The presence of various components in the needles was discovered through proximate analysis, including carbohydrates, crude protein, crude fiber, crude fat, ash, and moisture. Antinutrients such as chlorophyll, carotenoids, and vitamin A were confirmed. Needles are a rich source of mineral elements and contain significant levels of phenols, flavonoids, tannins, and phytosterols. Palmitic acid, 17-octadecynoic acid, and (Z)-18-octadec-9-enolide were the main components identified by GC-MS analysis. The methanolic extract exhibited substantial antioxidant capacity. The DPPH scavenging activity displayed a remarkable percentage inhibition. The integration of Abies marocana needles into sustainable diets can contribute to the well-being of humans and the planet, since the nutrient and bioactive compounds present have potential applications in the pharmaceutical and food industries.